2009
DOI: 10.1017/s1368980009991881
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of energy-restricted diets with different protein:carbohydrate ratios: the relationship to insulin sensitivity

Abstract: Objective: Insulin sensitivity could determine the effectiveness of weight-loss diets with different protein:carbohydrate ratios. Our aim was to evaluate whether or not energy-restricted diets with different protein:carbohydrate ratios in obese individuals with (IR) or without (IS) insulin resistance could lead to differences in weight loss or insulin sensitivity. Design: Prospective, randomized, clinical intervention study. Thirty-six obese patients, allocated to the IR or IS group after a 75 g oral glucose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 30 publications
0
27
0
1
Order By: Relevance
“…Evidence weighs heavily toward studies showing anthropometric benefits of increased protein intake [2,11-44]. Those that did not support additional benefits still showed that higher protein was equally as good as an alternative diet [45-60]. …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Evidence weighs heavily toward studies showing anthropometric benefits of increased protein intake [2,11-44]. Those that did not support additional benefits still showed that higher protein was equally as good as an alternative diet [45-60]. …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, protein intake spread between groups was often less than designed [45,46,48,57,61], a problem noted in a recent editorial [62]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations